2020
DOI: 10.3389/fpsyg.2020.01759
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Stress and Their Associations With Mental Disorders Among College Students: Results of the World Health Organization World Mental Health Surveys International College Student Initiative

Abstract: The college years are stressful for many students. Identifying the sources of stress and their relative importance in leading to clinically significant emotional problems may assist in the development of targeted stress management interventions. The current report examines the distribution and associations of perceived stress across major life areas with 12-month prevalence of common mental disorders in a cross-national sample of first-year college students. The 20,842 respondents were from 24 universities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 56 publications
(68 reference statements)
1
128
0
5
Order By: Relevance
“…Numerous worldwide studies were conducted to assess the level of perceived stress among University students before the COVID-19 pandemic (Shah et al, 2010 ; Borjalilu et al, 2015 ; Ahmed and Prashantha, 2018 ; Gazzaz et al, 2018 ; Al-Qahtani and Alsubaie, 2020 ; Karyotaki et al, 2020 ; Tariq et al, 2020 ), but only limited studies were conducted on the same issue during the COVID-19 outbreak. The available studies reported a high perceived stress level for students ranging from 12.6 to 30.2% during the current pandemic (AlAteeq et al, 2020 ; Pedrozo-Pupo et al, 2020 ; Sheroun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous worldwide studies were conducted to assess the level of perceived stress among University students before the COVID-19 pandemic (Shah et al, 2010 ; Borjalilu et al, 2015 ; Ahmed and Prashantha, 2018 ; Gazzaz et al, 2018 ; Al-Qahtani and Alsubaie, 2020 ; Karyotaki et al, 2020 ; Tariq et al, 2020 ), but only limited studies were conducted on the same issue during the COVID-19 outbreak. The available studies reported a high perceived stress level for students ranging from 12.6 to 30.2% during the current pandemic (AlAteeq et al, 2020 ; Pedrozo-Pupo et al, 2020 ; Sheroun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides suboptimal levels of mental health literacy [4], attitudinal barriers to utilize traditional (face-to-face) mental health services such as a preference to manage problems on one's own, desire for self-reliance or the fear of stigmatization, have been frequently observed among students, and appear to be more problematic than structural obstacles, such as limited access and costs [5][6][7]. On the other hand, recent research indicates that effective stress prevention could reduce up to 80% of the 12-month prevalence for mental disorders among university students [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mental disorders, university students commonly report experiencing stress. Further analyses of WMH-ICS initiative data from nine countries (24 universities) found that most students (93.7%) indicated some perceived stress within at least one of seven life domains relevant to university students (e.g., financial situation, love life, relationship with people at work/study), and that perceived extent of stress was associated with an increased odds of mental disorders [ 3 ]. University students may also face higher rates of psychological distress than non-university students.…”
Section: Introductionmentioning
confidence: 99%